Chapter Le fonti orali negli archivi di persona: descrizione, conservazione e fruizione - Stamuli, Maria Francesca (Strumenti per la didattica e la ricerca, 2021)
The contribution discusses oral sources, their use for historical and social research, their authenticity and reliability, considering the relevant perspective of legal protection.